Vocational Students' Mechanical Obedience within The Context of Teachers' Inured Behavior - Kaptan, Orhun; Korumaz, Mithat (TURKISH EDUCATION ASSOC, 2022)
Oppression devices in classroom discourse are the instruments of constructing vocational habitus through the mechanical obedience of students at vocational high schools (VHS). This phenomenological study investigates the awareness of oppression devices of dissident teachers in Turkey who are members of the same teachers' union whose vision is to protect and develop the economic, social, democratic, and cultural rights of education workers and to create a free democratic working life, together with the demand for a democratic and livable country. By means of thematic and critical discourse analysis of interviews, focus groups, and video recordings of both VHS students and teachers, we try to gain insight into teachers' consciousness of oppression devices in classroom discourse. This phenomenological study demonstrates that dissident teachers' classroom discourse adopts conscious and unconscious oppression devices under the burden of legitimized and oppressive external factors such as curriculum pressure, accountability, high-stakes testing, and organizational pressure. From this point of view, it is recommended to present experiences that can raise the awareness of educators at school about discourses that can deeply affect behaviors in the classroom.
Keywords: Mechanical obedience; Oppression devices; Pedagogy of poverty; Vocational habitus; The language of authority; Practical discourse; EDUCATION; TECHNOLOGY; Education & Educational Research